Docility and heifer pregnancy estimates in Angus heifers - White, Kari L.; Bormann, Jennifer M.; Moser, Daniel W.; Weaber, Robert L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Reproductive success is economically relevant in beef cattle operations because the number of calves born influences the value of calves sold at weaning. Improvements in reproductive performance can be up to four times more important than improvements in end-product traits in an operation selling calves at weaning. Selecting for fertility is difficult because it is influenced by a variety of factors. Temperament is one of the factors affecting fertility that requires further investigation. Researchers report that physiological responses associated with temperament can influence the probability of cows becoming pregnant. Stress hormones such as cortisol in the bloodstream can negatively affect the release of vital reproductive hormones. Methods have been developed to assess temperament in cattle. Beef Improvement Federation guidelines describe a temperament scoring system that has been adapted by breed associations for genetic evaluation of docility in cattle. The chute scoring system ranges from 1 to 6. A 1 or 2 score indicates highly acceptable behavior, 3 is average, and 4–6 is unacceptable. Studies have shown selection for cattle with a more favorable docility (chute) score would be effective in producing cattle with more acceptable dispositions. The docility expected progeny differences (EPD) reflect the probability that offspring will inherit genes for acceptable behavior, with a greater EPD associated with progeny exhibiting calmer behavior. Some breed associations have produced EPD rankings for docility. Docility measured by chute score has been found to be moderately heritable. The purpose of this research was to estimate the heritability and variance parameters for heifer pregnancy and docility in Angus cattle.
Keywords: Beef; Heifers; Fertility; Temperment; Heritability